2016
DOI: 10.3389/fncel.2016.00045
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Enhancement of Ethanol Intake in C57BL/6J Mice with a History of Chronic Ethanol Exposure: Involvement of Kappa Opioid Receptors

Abstract: Our laboratory has previously demonstrated that daily forced swim stress (FSS) prior to ethanol drinking sessions facilitates enhanced ethanol consumption in mice with a history of chronic intermittent ethanol (CIE) vapor exposure without altering ethanol intake in air-exposed controls. Because both stress and chronic ethanol exposure have been shown to activate the dynorphin/kappa opioid receptor (KOR) system, the present study was designed to explore a potential role for KORs in modulating stress effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 58 publications
(88 reference statements)
6
65
2
Order By: Relevance
“…Acute alcohol exposure leads to increased dopamine levels in the NAc, leading to rewarding effects, and KOP-r agonists oppose these effects by modulating the dopamine system [Lindholm et al 2007], suggesting a potential interaction between dopamine in the NAc and KOP-r activation by MSB in alcohol-related behavior. However, there are a number of studies that have found that classic KOP-r agonists increase alcohol drinking and reward [Anderson et al 2016; Rose et al 2016; Sperling et al 2010], and induce alcohol-seeking behavior in a reinstatement model [Funk et al 2014]. Therefore, our new data that the KOP-r agonist MSB reduces alcohol intake presents a scenario that is opposite to the results of previous studies using classic KOP-r agonists, thus warranting further study.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Acute alcohol exposure leads to increased dopamine levels in the NAc, leading to rewarding effects, and KOP-r agonists oppose these effects by modulating the dopamine system [Lindholm et al 2007], suggesting a potential interaction between dopamine in the NAc and KOP-r activation by MSB in alcohol-related behavior. However, there are a number of studies that have found that classic KOP-r agonists increase alcohol drinking and reward [Anderson et al 2016; Rose et al 2016; Sperling et al 2010], and induce alcohol-seeking behavior in a reinstatement model [Funk et al 2014]. Therefore, our new data that the KOP-r agonist MSB reduces alcohol intake presents a scenario that is opposite to the results of previous studies using classic KOP-r agonists, thus warranting further study.…”
Section: Discussioncontrasting
confidence: 67%
“…Specifically, activation of the kappa opioid receptor (KOP-r) system has been implicated in the negative reinforcing aspects of alcohol, opiate, and psychostimulant addictions [Herz 1997; Koob and Kreek 2007]. In rats and mice, acute administration of KOP-r agonists attenuates alcohol drinking [Sandi et al 1988; Lindholm et al 2001; Henderson-Redmond and Czachowski 2014], increases alcohol drinking [Anderson et al 2016; Rose et al 2016], and alters alcohol-induced conditioned place preference [Logrip et al 2009; Sperling et al 2010], while the selective KOP-r antagonist nor-binaltorphimine (nor-BNI) increases alcohol drinking in Lewis rats with relatively high intake [Mitchell et al 2005]. Recently KOP-r antagonists have been reported to attenuate stress-induced alcohol-seeking behavior in mice and rats [Sperling et al 2010; Deehan et al 2012; Funk et al 2014] and to reduce alcohol consumption in alcohol “dependent” rats [Walker and Koob 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Most recent experiments have been performed in a single strain – B6 – due to the robust enhancement in alcohol consumption and behavior observed in this strain following CIE (Lopez, Becker, & Chandler, 2014; Lopez, Griffin, Melendez, & Becker, 2012) and following CIE and exposure to additional environmental stressors (Anderson, Lopez, & Becker, 2016a). These studies demonstrate concomitant changes in neurotransmitters (Griffin, Ramachandra, Knackstedt, & Becker, 2015) and neuropeptides (Maldonado-Devincci et al, 2014) following CIE, and suggest alterations in specific circuits and regions (Anderson, Lopez, & Becker, 2016b; Lopez, Moorman, Aston-Jones, & Becker, 2016; Samantaray et al, 2015). Whether or not these changes are unique to B6 or represent common mechanisms in the addiction process remains an open question.…”
Section: Discussionmentioning
confidence: 64%
“…KOP-r/dynorphin activation is associated with the negative reinforcement aspects of alcohol addictions. It has been found that selective blockade of KOP-r attenuates excessive drinking, stress or cue -induced alcohol-seeking in mice and rats [Walker and Koob, 2008;Sperling et al, 2010;Deehan et al, 2012;Schank et al, 2012;Funk et al, 2014;Rorick-Kehn et al, 2014;Anderson et al, 2016;Zhou et al, 2017a] (but also see Mitchell et al, 2005;Sirohi et al, 2016). In line with these pharmacological results, alcohol drinking is decreased in KOP-r knockout mice [Kovacs et al, 2005].…”
Section: Kappa Opioid Receptor (Kop-r) and Dynorphin Systemmentioning
confidence: 90%